External environment effects on product innovation performance: the food and beverage industry in Istanbul - Erkman, Merve. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2013., 2013)
Product innovation performance is gaining importance in today's world along with increasing globalization and the developments in technology. Firms, even the biggest market leaders, do not possess all the internal skills, knowledge and capabilities needed to cope with global competition. Therefore, innovation can come from outside and large multinationals are moving towards a double network structure which makes external environment vital. Within this context, the primary objective of this thesis is to analyze the effects of some major factors and linkages related to the external environment of the firm on its product innovation performance. The factors are grouped as external knowledge inflow, cooperation with various external parties and international trade activities. To the best knowledge, literature lacks a study which'involves the analysis of all these specific factors in a single study. The framework developed is implemented on the food and beverage sector empirically. For this purpose, an extensive literature survey is conducted and related data is gathered using a questionnaire developed for this purpose. Utilizing statistical tests such as frequency, crosstab, correlation and regression, the impact of external environment are analyzed. This study can shed light on similar studies with the suggestion that external environment related various factors of the firm are worth analyzing in studying the product innovation performance offirms. The framework can also be implemented on companies from various sectors which would make it possible to benchmark sectors in terms of product innovation performance.
Keywords: Food industry and trade -- Turkey -- İstanbul.